The Role of Civic Education Teachers in Installing Character in the Next Generation - Handayani, Wiwik Tri (International Journal of Students Education, 2025)
Civic Education (PKn) has a strategic role in shaping the character of the next generation with integrity, ethics, and responsibility. PKn teachers not only function as teachers, but also as facilitators and role models in instilling moral and national values. This study aims to analyze the role of PKn teachers in instilling the character of the younger generation through an innovative and value-based learning approach. The research method uses a qualitative study approach where the basis of the discussion is obtained from the results of literature studies on book sources, previously existing relevant journals, and scientific articles to understand how teachers implement character learning strategies in schools. The results of the study show that PKn teachers play an important role in instilling values such as tolerance, discipline, honesty, and love of the homeland through interactive methods, critical discussions, and project-based learning. Support from the school environment, family, and community are also supporting factors for the success of character education. In conclusion, PKn teachers have a great responsibility in building the character of the next generation who are able to face global challenges while still upholding national values.